Identification of the gut bacteria of the greater wax moth - Betancourt, Oriana; Araneda, Ximena; Pesenti, Héctor; Anabalón, Leonardo (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
Throughout the world, the use of industrial polymers derived from fossil fuels is practically inevitable because they have such a wide range of applications; however, the environmental problems arising from this practice have led to a search for alternatives which will allow their use to be reduced, as well as strategies for their control by degradation using biorganic active agents. Insects have been a focus of special interest, as some species consume plastics and may serve to biodegrade them through the action of bacteria in their digestive tracts. In this context, the object of the present study was to characterise bacteria present in the intestine of wax moth larvae (Galleria mellonella). Thirty larvae were subjected to a diet based on polystyrene foam and thirty larvae in natural diet for 7 days. Gastrointestinal tracts were extracted and PCR was run. The results showed the presence of bacterial cells of Carnobacterium maltaromaticum, Brevibacterium sandarakinum, Pseudomonas psychrophila, Pseudomonas sp., Providence sp., Corynebacterium sp. However, the real action of these groups of bacteria in the effective degradation of polymers must be verified.